군소 섭취 후 발생한 독성간염 4예 - 송준화; Jun Hwa Song; 권태호; Tae Ho Kwon; 서정일; Jeong Ill Suh (The Korean journal of medicine, 2015)
저자들은 예전부터 해안가 지역에서 식용으로 사용되는 군소를 섭취하던 중 발생한 황달로 입원한 환자에서 임상적으로 독성간염을 진단하고 경과관찰 하였던 4예를 문헌고찰과 함께 보고하는 바이다. The sea hare is a marine mollusk in the family Aplysiidae that has long been consumed as food. Rarely, toxic hepatitis can occur after eating sea hare. We herein discuss four cases of toxic hepatitis due to sea hare ingestion and review the relevant literature. (Korean J Med 2015;88:680-684)